PENGARUH SUHU DAN LAMA PENYIMPANAN TERHADAP KANDUNGAN VITAMIN C PADA CABAI RAWIT PUTIH (CAPSICUM FRUSTESCENS) - RACHMAWATI, RANI; DEFIANI, MADE RIA; SURIANI, NI LUH (Jurnal Biologi Udayana, 2009)
The effect of temperature and length of storage on vitamin C concentration of chili (Capsicum frustescens) was observed on this study. Samples were taken from farmer’s field around Gianyar Regency of Bali. The chilies were treated with temperature such as 10ºC, 20ºC, and 29ºC (room temperature) and stored for 5, 10, and 15 days. Jacobs method was applied for vitamin C determination. The highest vitamin C content was obtain from control (59,9 mg/100 ml). On the other hand, the lowest was from chili that stored at room temperature for 15 days (23,6 mg/100 ml). For weight loss, the highest of loss was from chili which stored at room temperature for 15 days.
Keywords: Capsicum frustescens; storage; temperature; vitamin C